Home-state attachment and its effects. Issue 6 (10th September 2018) - Thakor, Mrugank; Reid, Susan; Chen, Rui
Abstract : Purpose: Many studies have investigated consumers' loyalty to businesses situated in the local area, in the community, the region or in the same country. However, the effect of loyalty to the state in which the consumer resides has received little attention. This paper aims to propose the concept of home-state attachment (HSA) and develop models of its antecedents and its effects on criterion variables such as loyalty to local business. Design/methodology/approach: After refinement of the measure of HSA, the authors conduct two studies ( n = 202 and n = 201) among residents of two different Canadian provinces (states). They estimate the models, which include both formative and reflective indicators, using structural equation modeling. Findings: The results of both studies show that HSA can be distinguished from related constructs like consumer ethnocentrism (CET). HSA has a strong effect on loyalty to local businesses, independent of the effect of CET, testifying to its importance. HSA also affects other criterion variables, with loyalty to local business playing a mediational role. Originality/value: This paper shows that HSA, a social-identity-based motivation for local patronage, is an important but largely overlooked determinant of loyalty to local businesses. The robustness of the results over two studies suggests that appeals to consumers based on this motivation may enhance the effectiveness of marketing programs.